2015
DOI: 10.5761/atcs.oa.14-00357
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Circadian Melatonin Levels on Inflammation and Neurocognitive Functions Following Coronary Bypass Surgery

Abstract: Purpose: In this study, the relationship between the plasma levels of melatonin and intercellular adhesion molecule-1 (ICAM-1), which plays role in several intercellular interactions including inflammatory and immune responses, and early neurocognitive functions associated with ischaemia-reperfusion injury during open heart surgery is examined. Methods: Forty patients who were to undergo elective coronary artery bypass grafting (CABG) were divided into two groups, those who underwent their operations at 8 AM (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Moreover, for patients with myocardial infarction, compared to daytime intervention, nighttime coronary intervention therapy has a poor prognosis (13). In addition, whether it is non cardiac surgery (14) or cardiac surgery (15), patients undergoing nighttime surgery are more likely to experience cognitive impairment and sleep disorders after surgery. Based on these evidence, it seems that performing surgery during the day, especially in the morning, is more advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for patients with myocardial infarction, compared to daytime intervention, nighttime coronary intervention therapy has a poor prognosis (13). In addition, whether it is non cardiac surgery (14) or cardiac surgery (15), patients undergoing nighttime surgery are more likely to experience cognitive impairment and sleep disorders after surgery. Based on these evidence, it seems that performing surgery during the day, especially in the morning, is more advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…MTN can reduce many undesirable disorders in patients with CABG. These effects are due to the antioxidant, anti-amyloid, and vasodilator effects of MTN 41 . In the study of Haghjooy et al, the effect of pre-CABG Melatonin administration on Nuclear Erythroid2-Related Factor 2 (Nrf2) activation was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hu et al showed that use of earplugs and eye masks improves sleep quality and nocturnal melatonin levels in a simulated ICU environment [ 20 ]. To our knowledge, the only study on the relation between melatonin secretion and surgical immune response has been conducted on patients who underwent coronary bypass surgery [ 21 ]. In this prospective study, it has been shown that melatonin levels in blood samples taken one hour before and four hours after the surgery, were higher in the group of patients who underwent surgery in the morning compared with the patients who were operated in the afternoon.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was actually consistent with the normal circadian rhythm of melatonin. Furthermore, authors have shown that, in the group with higher levels of melatonin, plasma ICAM-1 levels, an inflammatory marker, were reduced [ 21 ]. In the present study, preoperative samples were obtained two days before the surgery, which was independent from the timing of the procedure, thus, preoperative melatonin levels were similar in both groups.…”
Section: Discussionmentioning
confidence: 99%